Neonicotinoid concentrations in urine from chronic kidney disease patients in the North Central Region of Sri Lanka. Issue 1 (29th February 2016) - Kabata, Risako; Nanayakkara, Shanika; Senevirathna, Stmld; Harada, Kouji H.; Chandrajith, Rohana; Hitomi, Toshiaki; Abeysekera, Tilak; Takasuga, Takumi; Koizumi, Akio
Abstract : Neonicotinoid concentrations in urine from chronic kidney disease patients in the North Central Region of Sri Lanka: Risako Kabata, et al . Department of Health and Environmental Sciences, Graduate School of Medicine, Kyoto University Objective: Neonicotinoid insecticides have been widely used around the world since the 1990s. Reports have been made since the 1990s of rice paddy farmers in the North Central Region (NCR) of Sri Lanka suffering from chronic kidney disease with unknown etiology (CKDu). A preliminary evaluation of the exposure of local farmers in the NCR of Sri Lanka to neonicotinoids was performed. Methods: We analyzed neonicotinoid and neonicotinoid metabolite concentrations in spot urine samples. We selected 40 samples, 10 from farmers with CKDu and 10 from controls from each of two areas, Medawachchiya and Girandurukotte. Results: Imidacloprid and desmethyl‐acetamiprid were found at significantly higher concentrations in the control samples (with medians of 51 ng/l and 340 ng/l, respectively) than in the CKDu samples (medians of 15 ng/l and 150 ng/l, respectively) when the results were not adjusted for the creatinine contents. None of the six compounds that were measured in the urine samples were found at significantly higher concentrations in the CKDu samples than in the control samples. None of the neonicotinoid concentrations in the samples analyzed in this study exceeded the concentrations that have been found in samples from the general population of Japan. Conclusions: Farmers (both with and without CKDu) living in CKDu‐endemic areas in the NCR of Sri Lanka are exposed to lower neonicotinoid concentrations than non‐occupationally exposed residents of Japan.